EDUKASI FARMASI TERHADAP TINGKAT - Arifani Siswidiasari; Neni Probosiwi; Nur Fahma Laili; Sugeng Riyanto; Nurul Nurhanisah (Jurnal Buana Farma, 2023)
Asthma control level is one of the indicators to assess the success of asthma therapy. The provision of pharmaceutical education is crucial in changing respondents' attitudes in controlling and preventing recurrent asthma exacerbations. The type of research used is pre-experimental (One group pre-post-test design) which will be conducted through pre-testing first, then giving the intervention, and then providing a post-test to determine the changes that occur before and after the intervention. Data collection is done through interviews and filling out the Asthma Control Test questionnaire. In this study, a sample of 35 respondents was used. The research analysis was conducted using the Wilcoxon test. The demographic data results showed that the majority of respondents were female, 21 respondents (60%), aged 36-45 years, 14 respondents (40%), with high school education, 14 respondents (40%), occupation as a homemaker, 13 respondents (37.1%), and a history of asthma for more than 10 years, 13 respondents (37.1%). Out of 35 respondents, before receiving pharmaceutical education, there were 7 respondents (20%) well-controlled, 13 respondents (37.1%) partially controlled, and 15 respondents (42.9%) uncontrolled. The questionnaire results after providing education showed 12 respondents (34.3%) well-controlled, 17 respondents (48.6%) partially controlled, and 6 respondents (17.1%) uncontrolled. The statistical test results showed that there is an influence of pharmaceutical education on asthma control level with a significance value of 0.003.